Phosphoregulation of HORMA domain protein HIM-3 promotes asymmetric synaptonemal complex disassembly in meiotic prophase in Caenorhabditis elegans - Sato-Carlton, Aya; Nakamura-Tabuchi, Chihiro; Li, Xuan; Boog, Hendrik; Lehmer, Madison K.; Rosenberg, Scott C.; Barroso, Consuelo; Martinez-Perez, Enrique; Corbett, Kevin D.; Carlton, Peter Mark (PLoS Genetics, 2020)
In the two cell divisions of meiosis, diploid genomes are reduced into complementary haploid sets through the discrete, two-step removal of chromosome cohesion, a task carried out in most eukaryotes by protecting cohesion at the centromere until the second division. In eukaryotes without defined centromeres, however, alternative strategies have been innovated. The best-understood of these is found in the nematode Caenorhabditis elegans: after the single off-center crossover divides the chromosome into two segments, or arms, several chromosome-associated proteins or post-translational modifications become specifically partitioned to either the shorter or longer arm, where they promote the correct timing of cohesion loss through as-yet unknown mechanisms. Here, we investigate the meiotic axis HORMA-domain protein HIM-3 and show that it becomes phosphorylated at its C-terminus, within the conserved “closure motif” region bound by the related HORMA-domain proteins HTP-1 and HTP-2. Binding of HTP-2 is abrogated by phosphorylation of the closure motif in in vitro assays, strongly suggesting that in vivo phosphorylation of HIM-3 likely modulates the hierarchical structure of the chromosome axis. Phosphorylation of HIM-3 only occurs on synapsed chromosomes, and similarly to other previously-described phosphorylated proteins of the synaptonemal complex, becomes restricted to the short arm after designation of crossover sites. Regulation of HIM-3 phosphorylation status is required for timely disassembly of synaptonemal complex central elements from the long arm, and is also required for proper timing of HTP-1 and HTP-2 dissociation from the short arm. Phosphorylation of HIM-3 thus plays a role in establishing the identity of short and long arms, thereby contributing to the robustness of the two-step chromosome segregation.